Ruh al ma'aniy fi tafsir al Qur'an al 'azim wa al sabi' al mathaniy - Abi al Fadl Shihabuddin Sayyid Mahmud al Alusi al Baghdadi (Dar al Ihya' al Turath al 'Arabi)
ws.jl.1-3,5,7-14.c.1-2 jl.,4,6,8,15.c.1